The Transmogrification of St Bunnycrisp - Hunter, Catherine Jane (Centre for Film and Media Studies, 2016)
Into the life of cowardly Poppy comes a scary 6 foot tall talking rabbit whose job it is to give bullies a taste of their own medicine. But Poppy is a good girl, it's Jessica who's mean, who makes Poppy's life miserable, who gave Poppy the stupid rabbit as a 10th birthday present in the first place! But then he was just a soft-toy; not this monster in her closet. Did St. Bunnycrisp get sent to the wrong girl? On the way to finding the answers to these questions Poppy and St. Bunnycrisp become best friends and go on adventures in a parallel fantasy realm. That is until St. Bunnycrisp's fate is threatened by the cruel Icemaiden, and Poppy will have to find the courage to save her friends' lives on her own.